Desistance from crime and social and community (re)integration processes - Brunelle, Natacha (Understanding desistance from crime and social and community (re)integration, 2024)
This chapter lays the theoretical foundations for the (RE)SO 16-35 Partnership Research Program, in particular, Axis 1 of this programme as described in the Introduction to this book and from which the chapters of this collective of authors were written. The concepts of desistance from crime (primary, secondary, and tertiary), assisted desistance, and social and community (re)integration will be explained, after providing a context for the development of these concepts. The other chapters will present the theory and frameworks that underpin their specific subjects and objectives.